Prevalence of Substance Use among Youths in Selected Ward of Gadhi Rural Municipality, Sunsari, Nepal: A Descriptive Cross-sectional Study - Shrestha, Sharmila; Pradhan, Nirmala; Lamsal, Shyam; Sigdel, Rambha (Journal of BP Koirala Institute of Health Sciences, 2020)
Background: Tobacco and alcohol are the most prevalent substances in Nepal and their use is becoming a serious health problem. We aimed to find out the prevalence of substance use among youths and assess the association with selected demographic variables. Methods: A descriptive cross-sectional study was conducted among 813 youths residing in Gadhi Rural Municipality, ward number 1. The youths were selected through total enumerative sampling and eligible candidates were interviewed using semi-structured questionnaires on substance use. Data were analyzed using descriptive and inferential statistics. Results: Nearly 54% of the youths belonged to the age group 16-25 years and 51.2% were females. Tarai Janajati ethnic group represented 64.2%, and 99.8% were Hindu by religion. The prevalence of substance use was 26.4%. The majority of the youths (62.2%) had started the consumption of substances between the age of 13-20 years. Many (36.2%) had been using the substances for 6-10 years. Almost two-thirds (62.2%) had a family history of substance use. Curiosity was the main reason (29.7%) for the youths to consume the substance. Nearly 37% of the youths were found to be alcohol dependent. Age, sex, ethnicity, and income were significantly associated with substance use (p < 0.05). Conclusion: About one in every four youths was involved in substance use. In addition, it was more prevalent in male youths and the majority had started using substances at the age of 13 to 20 years.